Writing Manuals for the Masses The Rise of the Literary Advice Industry from Quill to Keyboard - Masschelein, Anneleen; de Geest, Dirk (New Directions in Book History, 2021)
This open access collection of essays examines the literary advice industry since its emergence in Anglo-American literary culture in the mid-nineteenth century within the context of the professionalization of the literary field and the continued debate on creative writing as art and craft. Often dismissed as commercial and stereotypical by authors and specialists alike, literary advice has nonetheless remained a flourishing business, embodying the unquestioned values of a literary system, but also functioning as a sign of a literary system in transition. Exploring the rise of new online amateur writing cultures in the twenty-first century, this collection of essays considers how literary advice proliferates globally, leading to new forms and genres.